Simulation Study of LPG Cooking Burner - Wichangarm, Mana; Matthujak, Anirut; Sriveerakul, Thanarath; Sucharitpwatskul, Sedthawatt; Phongthanapanich, Sutthisak (International Journal of Engineering and Technology, 2018)
The objective of this paper is to numerically study the flow feature and combustion phenomena of an energy-saving cooking burner using three-dimensional computational fluid dynamics (CFD). Combustion temperatures were experimentally and numerically investigated in order to not only validate the CFD model, but also describe the combustion phenomena. From the temperature comparison, the CFD model was good agreement with the experiment, having the error of less than 5.86%. Based upon the insight from the CFD model, the high temperature of 1,286 K occurred at the middle of the burner. The high intensive vortex of the flow being enhanced the combustion intensity and the heat transfer coefficient is obvious observed near the burner head inside the ring. Therefore, it is concluded that the burner ring is the major part since it controls flame structure, high temperature region, intensive combustion region, heat loss and suitable flow feature. However, heat transfer to the vessel should be further clarified by the CFD model.Â Â Â